1974
DOI: 10.2307/1935222
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Changes in Standing Crop and Primary Production in a Sedge Wetland and an Adjacent Dry Old‐Field in Central Minnesota

Abstract: Seasonal changes in above— and below—ground standing crop and primary production in a Carex rostrata wetland and an adjacent dry Poa pratensis old field were determined. Above ground, the Carex rostrata standing crop of green material varied from a minimum of 114 g/m2 frozen in the winter ice to a high of 852 g/m2 in late August. Maximum daily production averaged about 11 g/m2° day from mid—June to mid—July. Below—ground standing crop was highest in winter at 328 g/m2 in late July. Below—ground standing crop t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

1975
1975
2010
2010

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(29 citation statements)
references
References 27 publications
2
27
0
Order By: Relevance
“…Primary productivity is highly variable between sites and in different years for Sphagnum mosses, true mosses, forbs, shrubs, and trees (e.g., Wieder, 2006, and references therein) and for total site NPP (e.g., Rydin and Jeglum, 2006;Moore et al, 2002, and references therein). Relative NPP for the PFTs in HPM, and their sensitivities to water table depth and peat height are meant to represent general patterns common to northern peatlands (e.g., Walker, 1970;Reader and Stewart, 1972;Bernard, 1974;Forrest and Smith, 1975;Tallis, 1983;Backeus, 1990;Korhola, 1992;Rydin, 1993;Klinger and Short, 1996;Hughes and Barber, 2004;Leppälä, et al, 2008;Murphy et al, 2009;Murphy, 2009 and references therein). It is important to note that model NPP for a given water table and peat depth combines both plant abundances under those conditions as well as PFT inherent productivity per unit leaf biomass, so the defined optima and tolerance along water table and peat depth gradients represent PFT ecological niches instead of wider physiological niches.…”
Section: Vegetationmentioning
confidence: 99%
“…Primary productivity is highly variable between sites and in different years for Sphagnum mosses, true mosses, forbs, shrubs, and trees (e.g., Wieder, 2006, and references therein) and for total site NPP (e.g., Rydin and Jeglum, 2006;Moore et al, 2002, and references therein). Relative NPP for the PFTs in HPM, and their sensitivities to water table depth and peat height are meant to represent general patterns common to northern peatlands (e.g., Walker, 1970;Reader and Stewart, 1972;Bernard, 1974;Forrest and Smith, 1975;Tallis, 1983;Backeus, 1990;Korhola, 1992;Rydin, 1993;Klinger and Short, 1996;Hughes and Barber, 2004;Leppälä, et al, 2008;Murphy et al, 2009;Murphy, 2009 and references therein). It is important to note that model NPP for a given water table and peat depth combines both plant abundances under those conditions as well as PFT inherent productivity per unit leaf biomass, so the defined optima and tolerance along water table and peat depth gradients represent PFT ecological niches instead of wider physiological niches.…”
Section: Vegetationmentioning
confidence: 99%
“…Several species of sedge were identified in the meadows including: water sedge (Carex aquatilis), beaked sedge (Carex utriculata), Nebraska sedge (Carex nebrascensis), smallwing sedge (Carex rnicroptera), and fieldclustered sedge (Carex praegracilis). Water sedge, beaked sedge, and Nebraska sedge are water tolerant (Bernard, 1974(Bernard, , 1976Cronquist et al, 1977;Sjoberg and Danell, 1983;Grootjans and van Tooren, 1984), while smallwing sedge prefers moderately dry soils (Hermann, 1970), and fieldclustered sedge is intolerant of flooding and saturated soils (Gomm, 1978(Gomm, , 1979. Tufted hairgrass prefers moist soils, and may be restricted to these moist soils by competition from better adapted water-tolerant and dryland species (Davy and Taylor, 1974;Rahman and Rutter, 1980;Seliskar, 1983).…”
Section: Methodsmentioning
confidence: 99%
“…In contrast, yields of Kentucky bluegrass of 1,000 kg ha-' have been reported for dense swales by Wiegert and Evans (1964). Bernard (1974) compared peak yields of Kentucky bluegrass and Curex YOS truta to be 1 ,140 kg ha-' and 8,520 kg ha-', respectively. Manning et al (19891 demonstrated that root biomass of kentucky bluegrass was 7 times less than Cuvcx nebruskensis in the upper O-10 cm soil depth and more than 300 times less in the lo-20 cm depth.…”
Section: Value Of Native Aquatic Plantsmentioning
confidence: 99%
“…Reseeded species and other ruderal species replaced sedges and rushes on streambanks. These mesic species generally have a shallow and fine root system in contrast to the long, thick and fibrous roots of sedges (Bernard andGorham 1978, Manning et al 1989). Plants native to wetlands and streambanks are mostly water-loving species capable of withstanding prolonged periods of alternating wet and dry conditions (Rumburg and Sawyer 1965), an advantageous life strategy that most mesic graminoids lack.…”
Section: Dynamics Of Carex and Other Aquatic Plantsmentioning
confidence: 99%